2021
DOI: 10.3390/ijerph182413424
|View full text |Cite
|
Sign up to set email alerts
|

Response of Saudi Population to Strict Preventive Measures against COVID-19

Abstract: The Saudi ministry of health (MOH) started the preventive measures very early on before having a single case of COVID-19. There were very few studies regarding the awareness and adherence to the preventive measures against COVID-19 among the Saudi population in the literature. Objectives: The study aims to examine the awareness and commitment to the strict Saudi government preventive measures against COVID-19. Methods: A cross-sectional online survey targeted Saudi and non-Saudi populations aged 18+ in March–A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Consequently, the current phone-based Many studies conducted in Saudi Arabia illustrated the importance of awareness, attitude, and practice in society to reduce the virus spreading rate during pandemic. Our study results matching a recent study showed that the majority of the respondents were in favour of attitudes limiting the spread of COVID-19 like informing contacts, keeping precautionary measures, and choosing to stay at home and quarantine [21]. Another study re-ported that about 90% of the participants were aware of home quarantine and its duration [22].…”
Section: Discussionsupporting
confidence: 84%
“…Consequently, the current phone-based Many studies conducted in Saudi Arabia illustrated the importance of awareness, attitude, and practice in society to reduce the virus spreading rate during pandemic. Our study results matching a recent study showed that the majority of the respondents were in favour of attitudes limiting the spread of COVID-19 like informing contacts, keeping precautionary measures, and choosing to stay at home and quarantine [21]. Another study re-ported that about 90% of the participants were aware of home quarantine and its duration [22].…”
Section: Discussionsupporting
confidence: 84%
“…Continuous efforts should be maintained to sustain awareness among the public. Bin Abdulrahman/ Dec 2021 110 Response of Saudi Population to Strict Preventive Measures against COVID-19. 2958 participants Online questionnaire Most participants adhere to the strict government instructions regarding COVID-19 as they have to obey the law.…”
Section: The Searched Outcomesmentioning
confidence: 99%
“…The study by Shewale et al [39] found no relationship with stress or anxiety. Similarly, for the study by Bin Abdulrahman et al [32] conducted in Saudi Arabia, no correlation between participants' level of stress and their compliance with hygiene rules was found.…”
Section: Plos Onementioning
confidence: 80%
“…The distribution of scores by smoking status is described in Fig 3 . The lowest scores were recorded among students who use chicha (33 [27-39]), E cigarette (35 [31][32][33][34][35][36][37][38][39][40]) and especially those who use several forms of tobacco at the same time (31 [23-38.5]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation